2019
DOI: 10.1364/oe.27.002828
|View full text |Cite
|
Sign up to set email alerts
|

Eye safety implications of high harmonic generation in zinc selenide

Abstract: Polycrystalline zinc selenide (ZnSe) has been the subject of many nonlinear optics studies for wavelengths under 4.0 µm including sum/difference frequency generation, harmonic generation, and filamentation. In this report, the conversion efficiency of high harmonic generation (HHG) in ZnSe is quantified for mid-infrared wavelengths ranging from 2.7 µm to 8.0 µm. By increasing the fundamental wavelength, we demonstrate that HHG in thick ZnSe targets is limited by the band gap. The high conversion efficiency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Several recent publications have explored ZnS's and ZnSe's unusually strong nonlinear properties which allow it to undergo extremely efficient frequency conversion through harmonic generation and continuum broadening over a range of wavelengths spanning the mid-IR. [18][19][20][21] Using existing polycrystalline ZnSe plates, broadband continuum can be generated using material thicknesses as small as 3 to 10 mm. [18][19][20][21] A collaboration between the U.S. Army Research Laboratory, Ohio State University, the University of Arizona, and SURVICE Engineering Co. reported measurements of the nonlinearity of polycrystalline ZnSe ½n 2 ¼ ð1.2 AE 0.3Þ · 10 −14 cm 2 ∕W and ZnS ½n 2 ¼ ð5.0 AE 0.3Þ · 10 −15 cm 2 ∕W at 3.9 μm and demonstrated that simulations of the unidirectional pulse propagation equation with incorporated ionization effects could explain the broadband continuum generation experimentally observed in these media.…”
Section: Zns and Znse Materials As Continuum Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent publications have explored ZnS's and ZnSe's unusually strong nonlinear properties which allow it to undergo extremely efficient frequency conversion through harmonic generation and continuum broadening over a range of wavelengths spanning the mid-IR. [18][19][20][21] Using existing polycrystalline ZnSe plates, broadband continuum can be generated using material thicknesses as small as 3 to 10 mm. [18][19][20][21] A collaboration between the U.S. Army Research Laboratory, Ohio State University, the University of Arizona, and SURVICE Engineering Co. reported measurements of the nonlinearity of polycrystalline ZnSe ½n 2 ¼ ð1.2 AE 0.3Þ · 10 −14 cm 2 ∕W and ZnS ½n 2 ¼ ð5.0 AE 0.3Þ · 10 −15 cm 2 ∕W at 3.9 μm and demonstrated that simulations of the unidirectional pulse propagation equation with incorporated ionization effects could explain the broadband continuum generation experimentally observed in these media.…”
Section: Zns and Znse Materials As Continuum Sourcesmentioning
confidence: 99%
“…[18][19][20][21] Using existing polycrystalline ZnSe plates, broadband continuum can be generated using material thicknesses as small as 3 to 10 mm. [18][19][20][21] A collaboration between the U.S. Army Research Laboratory, Ohio State University, the University of Arizona, and SURVICE Engineering Co. reported measurements of the nonlinearity of polycrystalline ZnSe ½n 2 ¼ ð1.2 AE 0.3Þ · 10 −14 cm 2 ∕W and ZnS ½n 2 ¼ ð5.0 AE 0.3Þ · 10 −15 cm 2 ∕W at 3.9 μm and demonstrated that simulations of the unidirectional pulse propagation equation with incorporated ionization effects could explain the broadband continuum generation experimentally observed in these media. 22 While current studies have focused on polycrystalline ZnSe, Dr. Peter Schunemann (BAE Systems) detailed efforts to grow large single ZnSe and ZnS crystals through physical vapor transport and chemical vapor transport (CVT).…”
Section: Zns and Znse Materials As Continuum Sourcesmentioning
confidence: 99%
“…Eye safety standards such as ANSI Z136.1 set maximum permissible exposure (MPE) limits based on the laser wavelength and time duration, but they do not account for nonlinear processes altering the laser wavelength 23 . Concurrent studies of high harmonic generation in zinc selenide have shown the generation of sufficient visible and near-infrared radiation light from mid-IR source wavelengths to pose a retinal hazard by ANSI standards 24 . Eye safety standards inform the choice of laser eye protection (LEP) used by laser operators who choose LEP that absorbs or reflects the laser wavelength with the minimum reduction of visual acuity and color perception.…”
Section: Introductionmentioning
confidence: 99%